Effect of Lonicerae japonicae Flos Carbonisata-Derived Carbon Dots on Rat Models of Fever and Hypothermia Induced by Lipopolysaccharide - Wu J (Dove Medical Press, 2020)
Jiashu Wu,1 Meiling Zhang,1 Jinjun Cheng,1 Yue Zhang,2 Juan Luo,1 Yuhan Liu,1 Hui Kong,1 Huihua Qu,3 Yan Zhao1 1School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing 100029, People’s Republic of China; 2School of Science Life, Beijing University of Chinese Medicine, Beijing 100029, People’s Republic of China; 3Center of Scientific Experiment, Beijing University of Chinese Medicine, Beijing 100029, People’s Republic of ChinaCorrespondence: Yan Zhao Tel +86 010 6428 6705Fax +86 1 6428 6821Email zhaoyandr@163.comIntroduction: A correlation is established between the efficacy of Chinese herbal medicine and its charcoal drugs. Lonicerae japonicae Flos (LJF) is commonly used to treat fever, carbuncle, and tumors, among others. LJF Carbonisatas (LJFC) is preferred for detoxifying and relieving dysentery and its related symptoms. However, the mechanisms underlying the effects of LJFC remain unknown.Aim: The aim of this study was to explore the effects of LJFC-derived carbon dots (LJFC-CDs) on lipopolysaccharide (LPS)-induced fever and hypothermia rat models.Methods: LJFC-CDs were characterized using transmission electron microscopy, high-resolution transmission electron microscopy, Fourier-transform infrared, ultraviolet, fluorescence, X-ray photoelectron spectroscopy, X-ray diffraction and high-performance liquid chromatography. The anti-inflammatory effects of LJFC-CDs were evaluated and confirmed using rat models of LPS-induced fever or hypothermia.Results: The LJFC-CDs ranged from 1.0 to 10.0 nm in diameter, with a yield of 0.5%. LJFC-CDs alleviated LPS-induced inflammation, as demonstrated by the expression of tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 and the recovery of normal body temperature.Conclusion: LJFC-CDs may have an anti-inflammatory effect and a potential to alleviate fever and hypothermia caused by inflammation.Keywords: carbon dots, Lonicerae japonicae Flos, anti-inflammatory, lipopolysaccharide